Investigation on mechanical properties of ABS using rapid rpototyping technology and injection molding process - Wan Yusoff, Wan Ahmad Yusmawiza; Syazmi, Khairil; Mohd Naeem, Saripan (2009)
This paper is an explanation of the mechanical properties of ABS material by using different process and technology of producing it. The main concern is to expose the user about the importance of differentiating two main production machines of plastics which are rapid prototyping technology and injection molding process. The results of the experiment will be fully used to evaluate the advantages and the disadvantages of these two technologies. The machines used throughout the completion of this project are; using the rapid prototyping machine and the injection molding machine. The material used is Acrylonitrile Butadiene Styrene (ABS); a terpolymer of acrylonitrile, butadiene and styrene. The methods and processes of preparing this report are done by conducting several researches’ from the book, journals and newspapers, discussing with the supervisor of the project, producing the products at the respective laboratories and accessing the information through the internet. Further investigation to get the results in order to complete this task is obtained by conducting the tensile and bending tests towards the products under the supervision from the experts From the report, the user should be able to evaluate both processes and at the same time, select which is the best method that should be applied and implemented in the modern use of technology. The application of both mentioned technology must be observed and used in accordance to give effectiveness at the first place.